The Economics of First-Contract Mediation - Sabien Dobbelaere; Roland Iwan Luttens (Institute for the Study of Labor (IZA), 2013)
This paper provides an economic foundation for non-binding mediation to stimulate first collective bargaining agreements, as implemented in British Columbia since 1993. We show that the outcome of first-contract mediation is Pareto efficient and proves immune to the insider-outsider problem of underhiring. We also demonstrate that equilibrium wages and profits under mediation coincide with the Owen values of the corresponding cooperative game with the coalitional structure that follows from unionization.
Keywords: C71; J51; L20; K12; 330; BC first-contract model; mediation; collective bargaining; union; non-binding contract